Hubungan mekanisme koping dengan perilaku Agresif remaja - Meutia - Rhadia; Fathra Annis Nauli; Arneliwati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Coping mechanisms are individual response to situation that threaten their physically and psychologically. If coping mechanisms used not solve the difficulties well but adds difficulties and conflict, tension, fear and anxiety wich can eventually lead to aggressive behavior. This research aims at examining the correlation between coping mecanisms with adolescent aggressive behavior. It used the description correlation method with cross sectional approach. The number of samples was 89 respondents that usedsystematic random sampling method. The instrument used was questionnaire that has been tested for validity and reliability. The data was analyzed by using univariate analysis and bivariate analysis. From the statistic data, ρ value (0,004) < α (0.05). It means that there is correlation between coping mecanisms with adolescent aggressive behavior at vocational high school 2 Pekanbaru Keywords : Adolescence, aggression behavior, coping mechanisms.